Program Ilqa Kalimah sebagai penguatan karakter religius di Mafaza Imam Bukhari Boarding School - Gastiadirrijal, Wayan; Kosasih, Aceng; Abdullah, Mulyana (Program Studi Magister Pendidikan Agama Islam, 2026)
Strengthening religious character has become a crucial issue in Islamic education, particularly amidst the increasing phenomenon of moral degradation in the modern era, characterized by a decline in students' ethics, responsibility, and courtesy. This study aims to thoroughly examine the implementation of the Ilqa Kalimah Program as a strategy for strengthening religious character while enhancing the language proficiency of santri (students) at Mafaza Imam Bukhari Boarding School. This research employs a qualitative approach with a case study design. The research subjects comprise the boarding school leadership, program supervisors, and students directly involved in the execution of Ilqa Kalimah. Data collection techniques included participatory observation, in-depth interviews, and documentation studies. Data analysis was conducted through data reduction, data display, and conclusion drawing, with data validity established using source and technique triangulation. The results indicate that the Ilqa Kalimah Program is implemented systematically and integrated with worship habituation, the language environment, and religious literacy. The program effectively plays a role in shaping students' religious character—such as discipline, responsibility, spiritual awareness, and communication ethics—while simultaneously improving speaking skills in Arabic and English. Thus, the Ilqa Kalimah Program can be viewed as a relevant and adaptive religious-linguistic educational model in addressing the challenges of moral degradation in the modern educational environment. Abstrak Penguatan karakter religius menjadi isu krusial dalam dunia pendidikan Islam, khususnya di tengah meningkatnya fenomena degradasi moral pada era modern yang ditandai dengan melemahnya etika, tanggung jawab, dan kesantunan peserta didik. Penelitian ini bertujuan untuk mengkaji secara mendalam implementasi Program Ilqa Kalimah sebagai strategi penguatan karakter religius sekaligus peningkatan kecakapan berbahasa santri di Mafaza Imam Bukhari Boarding School. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus. Subjek penelitian terdiri atas pimpinan pesantren, ustadz pembina program, dan santri yang terlibat secara langsung dalam pelaksanaan Ilqa Kalimah. Teknik pengumpulan data meliputi observasi partisipatif, wawancara mendalam, dan studi dokumentasi. Analisis data dilakukan melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan, dengan pengujian keabsahan data menggunakan triangulasi sumber dan teknik. Hasil penelitian menunjukkan bahwa Program Ilqa Kalimah diimplementasikan secara sistematis dan terintegrasi dengan pembiasaan ibadah, lingkungan bahasa, serta literasi keagamaan. Program ini berperan efektif dalam membentuk karakter religius santri, seperti kedisiplinan, tanggung jawab, kesadaran spiritual, dan etika komunikasi, sekaligus meningkatkan kemampuan berbicara dalam bahasa Arab dan Inggris. Dengan demikian, Program Ilqa Kalimah dapat dipandang sebagai model pendidikan religius-linguistik yang relevan dan adaptif dalam menjawab tantangan degradasi moral di lingkungan pendidikan modern.